Human Glycolipid Transfer Protein (GLTP) Expression Modulates Cell Shape - Gao, Yongguang (Public Library of Science, 2011)
Glycolipid transfer protein (GLTP) accelerates glycosphingolipid (GSL) intermembrane transfer via a unique lipid transfer/binding fold (GLTP-fold) that defines the GLTP superfamily and is the prototype for GLTP-like domains in larger proteins, i.e. phosphoinositol 4-phosphate adaptor protein-2 (FAPP2). Although GLTP-folds are known to play roles in the nonvesicular intracellular trafficking of glycolipids, their ability to alter cell phenotype remains unexplored. In the present study, overexpression of human glycolipid transfer protein (GLTP) was found to dramatically alter cell phenotype, with cells becoming round between 24 and 48 h after transfection. By 48 h post transfection, ∼70% conversion to the markedly round shape was evident in HeLa and HEK-293 cells, but not in A549 cells. In contrast, overexpression of W96A-GLTP, a liganding-site point mutant with abrogated ability to transfer glycolipid, did not alter cell shape. The round adherent cells exhibited diminished motility in wound healing assays and an inability to endocytose cholera toxin but remained viable and showed little increase in apoptosis as assessed by poly(ADP-ribose) polymerase cleavage. A round cell phenotype also was induced by overexpression of FAPP2, which binds/transfers glycolipid via its C-terminal GLTP-like fold, but not by a plant GLTP ortholog (ACD11), which is incapable of glycolipid binding/transfer. Screening for human protein partners of GLTP by yeast two hybrid screening and by immuno-pulldown analyses revealed regulation of the GLTP-induced cell rounding response by interaction with δ-catenin. Remarkably, while δ-catenin overexpression alone induced dendritic outgrowths, coexpression of GLTP along with δ-catenin accelerated transition to the rounded phenotype. The findings represent the first known phenotypic changes triggered by GLTP overexpression and regulated by direct interaction with a p120-catenin protein family member.